2011
DOI: 10.1021/am200532j
|View full text |Cite
|
Sign up to set email alerts
|

A Biomimetic Approach to Enhancing Interfacial Interactions: Polydopamine-Coated Clay as Reinforcement for Epoxy Resin

Abstract: A facile biomimetic method was developed to enhance the interfacial interaction in polymer-layered silicate nanocomposites. By mimicking mussel adhesive proteins, a monolayer of polydopamine was constructed on clay surface by a controllable coating method. The modified clay (D-clay) was incorporated into an epoxy resin, it is found that the strong interfacial interactions brought by the polydopamine benefits not only the dispersion of the D-clay in the epoxy but also the effective interfacial stress transfer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
191
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(192 citation statements)
references
References 43 publications
(52 reference statements)
1
191
0
Order By: Relevance
“…20 The greater improvement of the properties at 0.2% can be explained by the dispersion of the clay platelets. This dispersion causes a higher gain in surface area of these particles, thus producing a larger polymer/nanofiller interfacial area, [21][22][23] which enables most of the atoms on the surface to participate in the interaction between the phases, facilitating the transmission of forces between them and increasing the strengthening effect. This behavior is similar to that observed in other nanofillers.…”
Section: Discussionmentioning
confidence: 99%
“…20 The greater improvement of the properties at 0.2% can be explained by the dispersion of the clay platelets. This dispersion causes a higher gain in surface area of these particles, thus producing a larger polymer/nanofiller interfacial area, [21][22][23] which enables most of the atoms on the surface to participate in the interaction between the phases, facilitating the transmission of forces between them and increasing the strengthening effect. This behavior is similar to that observed in other nanofillers.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 For epoxy mixtures with varying HBPSi-2 loadings, the viscosity of the mixture decreases as the HBPSi-2 loading increases, indicating an improved owability aer the addition of HBPSi-2 ( Fig. 2(b)).…”
Section: Rheology Of Modied Systemmentioning
confidence: 97%
“…14 polydopamine anchored on the surface of a variety of materials. [6][7][8][9] For example, Lee et al studied the dopamine polymerization and coating function on the surface of different organic (e.g., polyethylene) and inorganic materials. 6 The results showed that there were a lot of oxygen-containing groups on the dopamine oxidation film surface on polyethylene with good adhesion properties.…”
Section: Introductionmentioning
confidence: 99%